Application of coercimetry to assess the functional properties of materials - Kostin Vladimir (EDP Sciences, 2021)
The purpose of this work is a comparative study of the possibilities of various types of coercimeters to assess the functional properties of ferromagnetic materials. Conducted research have shown that the limitation of the maximum measured value of the coercive force using an attached transducer with a U-shaped electromagnet is due to the lower value of the magnetic resistance of the tested workpiece. The upper limit of measurements of the coercive force using a two-pole transducer is determined by the magnitude of the tangential component of the magnetic field only by the possibility of magnetizing the tested object.